Religious education via Arabic language module - Usop, Mohd Puzhi; Seman, Mohammad (2010)
It is a known fact that Arabic language is essential in Islam. The appointment of the Last Prophet Muhammad p.b.u.h. from the Arabs and the revelation of Al-Quran Al-Kareem in the Arabic language have made it widespread all over the world. Furthermore, Islam has determined the usage of Arabic language as the medium in 'ibadah' for the Muslims. For the Arabs, this is an advantage to them because it is their mother tongue. They can speak, read and comprehend the language very well. But for non-Arabs, no matter what race, ethnic and citizenship they are, they cannot use their own languages in their 'ibadah'. They must use the Arabic Language in their daily obligations ('ibadah'). It is very important for Muslims, not only to be able to read, but also to be able to understand, to comprehend and to realize whatever is said in their daily 'ibadah'. As such, all Muslims must learn the Arabic language. This is the only way that will help them to improve the quality of their daily 'ibadah'. Memorization itself is not enough. Muslims have to spend their time learning the language. Therefore, the researchers are presenting here fundamentals, guidelines, methods, approaches and finally the module for religious education which they hope will benefit the 'ummah'. It should be noted that many Muslims do not understand what they read or recite in their daily ‘ibadah’. The religious education via Arabic language, which specially focuses on 'ibadah’ or daily obligation, should be designed to solve the problem. Keyword : Learning Arabic Language for ibadah purposes